'The king and the bishops have much to offer': episcopal appointments and the legitimacy conflict over the archiepiscopal see of Reims (989‐99). Issue 4 (23rd October 2020) - Lisson, Jelle
Abstract : At the end of the tenth century, two clerics laid claim to the archiepiscopal see of Reims: Arnulf of Reims and Gerbert of Aurillac. This episode constitutes an unprecedented opportunity to explore episcopal appointments, because of the survival of three lengthy narratives: the council acts of Saint‐Basle (991), Gerbert's letter collection and the Historiae of Richer of Reims. The primary goal of this article is to coax out the many parties involved in the decision‐making process preceding an episcopal appointment as well as the multifaceted, volatile ties between these participants. This enables us to identify their strategies and motives beyond the dichotomy between Carolingian and Capetian royal power, and beyond formulaic records in narrative, diplomatic and epistolary sources that merely echo canon law .